Development and Initial Evaluation of the ClearSpeak Style for Automated Speaking of Algebra. Issue 2 (18th August 2016) - Frankel, Lois; Brownstein, Beth; Soiffer, Neil; Hansen, Eric
Abstract: The work described in this report is the first phase of a project to provide easy‐to‐use tools for authoring and rendering secondary‐school algebra‐level math expressions in synthesized speech that is useful for students with blindness or low vision. This report describes the initial development, software implementation, and evaluation of the ClearSpeak speech style—implemented for initial testing purposes using prerecorded synthetic speech, and implemented later in the project as a collection of predefined rules and in some cases variations (called preferences in ClearSpeak)—for automatically generated synthetic speech. In addition to wording, speech styles can specify pausing (or other prosodic cues) within the speech. The ClearSpeak style focuses on speech for secondary school algebra. The evaluation compares a prototype of the ClearSpeak style to two pre‐existing speech styles: MathSpeak and SimpleSpeak. The primary parameters evaluated are students' success in drawing conclusions about the content and structure of math expressions and their perceptions regarding the familiarity, helpfulness, and understandability of the expressions as spoken. Please see Appendix E for information on obtaining a version of this report that is fully accessible using the tools described. Abstract : Report Number: ETS RR‐16–23